If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x=10-2x=
We move all terms to the left:
3x-(10-2x)=0
We add all the numbers together, and all the variables
3x-(-2x+10)=0
We get rid of parentheses
3x+2x-10=0
We add all the numbers together, and all the variables
5x-10=0
We move all terms containing x to the left, all other terms to the right
5x=10
x=10/5
x=2
| 115=-16t^2 | | 6n+8=1-2 | | 12x−7=11x−19, | | -15=5(k+4) | | -15=5(k+4 | | 4x^2-x^2+2=0 | | x^2-6x-16=11 | | 4x+5x-2x=4(7)x= | | -10-4(6-3x)^1/4=-22 | | 1/(3^x)=3^3 | | 3.2+8x=9×-5.1 | | 41−7y=11 | | 24/384=60/m | | 6/t=3/4 | | 3m+5=20.m | | 3m+2m=7 | | 1.8/x=9/3.5 | | 7x+35=-105 | | 5x+5=-14+2x | | p^2+18p-40=0 | | 2(t+13)10+t=1 | | 3p/10+7=p/2+5 | | 12x=30-3x= | | 5x+2=4x+6) | | a-680=137 | | 8-f=17 | | 3(2x+5=-21 | | √-8x+12=10 | | 8x+44=7(x+3) | | -10(x-7)=10-10x | | 2c^2-10c-8=0 | | x^2-10=182 |